Preparation method and application of ionic liquid loaded resin
The preparation method of glycine ionic liquid-loaded resin solves the complexity and environmental pollution problems of liquid-liquid extraction in wet-process phosphoric acid production, and realizes efficient and environmentally friendly phosphorus resource recovery and reuse.
Patent Information
- Application Number
- CN202411026809.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2025-09-09
- Estimated Expiration
- 2044-07-30
AI Technical Summary
The liquid-liquid extraction process in existing wet-process phosphoric acid production is complex, the ion separation efficiency is low and it is easy to emulsify. The use of traditional solvents is not environmentally friendly, making it difficult to achieve efficient and environmentally friendly phosphorus resource recovery.
The preparation method of glycine ionic liquid loaded resin is adopted. Through the chemical grafting reaction of chloromethylated polystyrene resin and glycine solution, combined with auxiliary microspheres and vacuum drying process, a stable ionic liquid loaded resin is prepared for selective adsorption of phosphoric acid, and desorption treatment is carried out using sulfuric acid solution.
The recovery rate of phosphoric acid is improved, emulsification and solvent loss are avoided, environmental pollution is reduced, the process flow is simplified, production efficiency and economic benefits are improved, and the service life of the material is extended.
Smart Images

Figure CN119019581B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of resin preparation, and in particular to a preparation method and application of an ionic liquid loaded resin. Background Art
[0002] As a new type of composite material, ionic liquid-loaded resin combines the unique properties of ionic liquids and the porous structure of resins, and is widely used in catalysis, adsorption, electrochemistry and green chemical synthesis.
[0003] Ionic liquid-loaded resins are synthesized by chemically grafting ionic liquids onto polymers. Due to their excellent cleanliness, high cyclic stability, and exceptional selectivity, they are considered a promising new adsorption material. Their cleanliness is due to the fact that, compared to traditional liquid-liquid extraction, ionic liquid-loaded resins have a lower environmental impact, avoiding the volatilization of organic solvents and preventing turbidity and emulsification of the solution phase. Their selectivity stems from the fact that ionic liquid-loaded resins with varying functional groups can be prepared using different chemical reagents and chemical grafting methods, allowing the design of ionic liquid-loaded resins with varying selectivities.
[0004] Ionic liquid-loaded resins are prepared by chemical grafting, and a strong chemical bond can be formed between the ionic liquid and the resin, thereby significantly reducing the loss of ionic liquid during the adsorption and desorption processes. This also ensures that the ionic liquid-loaded resins have better cyclic stability. Usually, the adsorption amount decreases by about 1% after every ten cycles, which is much lower than that of traditional solvent-impregnated resins.
[0005] Phosphorus resource processing mainly includes thermal and wet processes. The sulfuric acid process, a mainstream wet-process phosphoric acid process, is simple, highly adaptable to ore, and suitable for large-scale industrial production. However, conventional liquid-liquid extraction (LILE) is complex, has low ion separation efficiency, and is prone to emulsification of the extractant, making phase separation difficult. Using ionic liquid-loaded resins to adsorb phosphorus from wet-process phosphoric acid avoids these issues. Summary of the Invention
[0006] In order to solve the above problems, the present invention provides a preparation method and application of an ionic liquid-loaded resin.
[0007] The technical solution of the present invention is: a method for preparing an ionic liquid-loaded resin, comprising the following steps:
[0008] S1. Pretreatment of chloromethylated polystyrene resin
[0009] Soaking the chloromethylated polystyrene resin in an ethanol solution at a ratio of 1:1.5-2.5 g / ml for 2-3 hours, washing, and drying to obtain a pretreated chloromethylated polystyrene resin;
[0010] S2. Prepare glycine solution
[0011] Mixing glycine with water and stirring until completely dissolved to obtain a glycine solution with a mass concentration of 10 to 30%;
[0012] S3. Preparation of ionic liquid loaded resin
[0013] The pretreated chloromethylated polystyrene resin and glycine solution are introduced into a reactor at a ratio of 1:20-60 g / ml, heated and stirred using a constant temperature magnetic stirrer at a heating temperature of 65-105° C. and a stirring time of 6-30 hours. After the synthesis reaction is completed, the resin is cooled, the solid-liquid mixture in the reactor is solid-liquid separated, and the filtered solid matter is washed with deionized water, and then placed in a vacuum drying oven for drying to obtain an ionic liquid-loaded resin.
[0014] Description: Using glycine ionic liquid-loaded resin to purify phosphoric acid offers higher recovery rates than traditional liquid-liquid extraction processes, avoids emulsification, reduces solvent loss, and is environmentally friendly with good recyclability. The solvents used are primarily water and ethanol, which are more environmentally friendly than traditional volatile organic solvents, reducing environmental pollution. Deionized water washing and vacuum drying effectively remove residual impurities and solvents, further minimizing environmental impact. The process utilizes low-cost raw materials and mild reaction conditions, reducing production costs. High recovery rates and product purity minimize raw material waste and improve economic efficiency.
[0015] Furthermore, the mixing ratio of the ethanol solution and the chloromethylated polystyrene resin in S1 is 1.5-2.5:1 ml / g; the mixing and soaking time is 2-3 hours; the volume concentration of the ethanol solution is 95-99%; and the washing and drying method is: soaking in deionized water for 1-2 hours, then washing the chloromethylated polystyrene resin with deionized water, and then placing the washed chloromethylated polystyrene resin in a vacuum drying oven and drying it at a temperature of 55-65°C for 4-5 hours.
[0016] Description: The mixing ratio ensures that the ethanol solution can fully wet the chloromethylated polystyrene resin, effectively treating its surface and internal pores; an appropriate amount of solvent helps the resin react evenly, avoiding uneven reaction caused by local over-concentration or over-diluted solution; high-concentration ethanol has a strong dissolving ability and can effectively remove impurities and impurities on the resin surface; deionized water washing: deionized water can effectively remove salts and other water-soluble impurities on the resin surface, ensuring the purity of the resin; vacuum drying: a vacuum environment accelerates solvent evaporation, and a temperature range of 55-65°C can quickly dry the resin without damaging its structure.
[0017] Furthermore, the solid-liquid separation method described in S3 is: filtering the solid-liquid mixture in the reactor with quantitative medium-speed filter paper, and when no obvious liquid drips out of the filter paper, washing the filtered solid matter with deionized water by flushing for 8 to 12 times to complete the solid-liquid separation of the ionic liquid loaded resin.
[0018] Description: The use of quantitative medium-speed filter paper can effectively separate solid-liquid mixtures in a relatively short time, improving production efficiency. No obvious liquid dripping occurs after filtration. This step ensures that most of the liquid is filtered out, reducing solvent residue in the subsequent washing process and improving product purity. Multiple washings ensure that residual solvent and impurities attached to the solid surface are completely removed, further improving product purity and quality. The use of deionized water rinsing is relatively gentle and will not damage the structure of the ionic liquid-loaded resin, maintaining the integrity and performance of the product.
[0019] Furthermore, the chloromethylated polystyrene resin in S1 is in the form of particles with a particle size of 100 to 200 μm.
[0020] Description: Resin particles with a particle size of 100 to 200 μm have a large surface area, which is conducive to full contact with the glycine solution and improves the reaction efficiency. Particles of this size are easy to disperse evenly during the reaction, reducing local uneven reactions. Particles of this size are easier to handle during filtration and washing, reducing the difficulty of handling.
[0021] Furthermore, auxiliary microspheres are added to the reactor in step S3 at a mass ratio of 2 to 25% of the pretreated chloromethylated polystyrene resin;
[0022] The auxiliary microspheres are prepared by mixing sterile absorbent cotton and a sulfuric acid solution with a volume concentration of 45-55% in a mass ratio of 4:5-7, stirring and hydrolyzing at a temperature of 40-50°C; adding water to a mixed solution obtained after the hydrolysis is completed, with the mass ratio of the mixed solution to water being 1:8-12; standing for 10-12 hours, removing the supernatant, and centrifuging the remaining mixed solution; filtering and washing with deionized water and a filter membrane, adding TMOS accounting for 3-5% of the mass of the mixed solution when the pH reaches 2.4, stirring for 1-3 hours, introducing the mixed solution into a spherical mold with an average particle size of 2-3 mm for freeze molding, and demolding at 500-550°C to obtain aerogel particles; immersing the aerogel particles in a solution of lanthanum nitrate hexahydrate with a concentration of 5-30%, heating in a water bath at 50-70°C for 25-35 hours, and drying and calcining for 5-7 hours to obtain the auxiliary microspheres.
[0023] Description: During the synthesis of the ionic liquid-loaded resin, auxiliary microspheres are added to the resin and mixed with sterile absorbent cotton and hydrolyzed with sulfuric acid solution to form a stable fiber structure, laying the foundation for subsequent aerogel preparation. Impurities are removed by washing and centrifugation to improve the purity of the aerogel. The addition of TMOS enhances the mechanical strength and chemical stability of the aerogel, allowing the preparation of aerogel particles with good shape retention. The lanthanum element from lanthanum nitrate hexahydrate is uniformly incorporated into the aerogel composite resin material through soaking and heating, increasing the composite resin's functionality for phosphate ion adsorption. The presence of auxiliary microspheres increases the surface area of the reaction system, promoting contact between reactants and improving reaction efficiency. The lanthanum element in the auxiliary microspheres can impart new properties to the product and increase adsorption capacity. The dispersion of the two is improved and agglomeration is reduced. At the same time, the incorporation of particles can also enhance the active area of the ionic liquid-loaded resin during the adsorption of phosphate. The auxiliary microspheres can improve the mechanical and thermal stability of the composite resin material, extending its service life.
[0024] Furthermore, the stirring hydrolysis time is 1.5 to 2.5 hours, the stirring rate is 200 to 400 rpm; the centrifugal speed is 10,000 to 11,000 rpm; the freeze-molding method is: placing the spherical mold at -5 to 8°C for freeze molding for 4 to 6 hours, and then placing it in a freeze dryer at -75 to 95°C for freeze drying for 25 to 35 hours; the drying temperature is 70 to 90°C, the drying time is 0.5 to 3 hours, and the calcination temperature is 500 to 600°C.
[0025] Description: Proper stirring ensures uniform mixing of reactants, promotes the hydrolysis reaction, and thus improves product quality and yield. Controlling the stirring rate influences mass and heat transfer in the reaction system, helping to form uniform particles or structures. High centrifugal speeds facilitate rapid separation of solids and liquids, reducing separation time and improving separation efficiency. Furthermore, appropriate centrifugal speeds ensure that solid particles are not destroyed, preserving their integrity and morphology. Freeze-molding at low temperatures creates a uniform microstructure, while freeze-drying removes moisture without destroying the material's structure. This method is particularly suitable for preparing heat-sensitive materials, such as biological products or pharmaceuticals. Appropriate drying temperature and time ensure complete removal of moisture from the material while preventing damage from overheating. The drying process helps improve the material's stability and shelf life. Calcination removes organic matter and moisture from the material while promoting the crystallization of inorganic compounds. Appropriate calcination temperatures enhance the material's chemical stability and mechanical strength.
[0026] The ionic liquid loaded resin prepared by the method is applied to selectively adsorb phosphorus, and the application method is as follows:
[0027] Furthermore, the prepared ionic liquid-loaded resin is placed in a multi-metal ion solution with a concentration of 4.5 mol / L, and oscillation adsorption is performed at an oscillation frequency of 110 to 130 r / min. The mixing ratio of the phosphoric acid solution and the ionic liquid-loaded resin is 20 to 60:1 ml / g, the temperature is maintained at 25 to 35°C, and the adsorption time is 4 to 8 hours. Then, solid-liquid separation is performed, and finally, the extracted phosphoric acid-containing ionic liquid-loaded resin is desorbed to obtain a phosphoric acid-containing solution. The multi-metal ion solution is an aqueous solution of metal ions containing iron, magnesium, aluminum, and phosphorus.
[0028] Description: When the oscillation frequency is within this range, sufficient contact between the resin particles and the multi-metal ion solution can be ensured, thereby improving the adsorption efficiency; a reasonable mixing ratio ensures that the resin can fully adsorb phosphoric acid, avoiding incomplete adsorption caused by excessive solution; the mixing ratio within this range can make the resin particles fully immersed in the phosphoric acid solution, thereby achieving efficient adsorption; the temperature range of this method is most suitable for phosphoric acid adsorption, which can improve the adsorption rate and efficiency while avoiding damage to the resin structure caused by excessive temperature; within this adsorption time period, the resin particles have sufficient time to react with the phosphoric acid solution, thereby achieving a high adsorption rate; the adsorbed phosphoric acid is desorbed from the resin and can be recycled, reducing costs and reducing environmental pollution; through the above steps.
[0029] Furthermore, the desorption treatment method is: using a sulfuric acid solution with a concentration of 4 to 6 mol / L as a desorbent, mixing the phosphoric acid-containing ionic liquid-loaded resin and the sulfuric acid solution in a volume ratio of 1:28 to 32 for desorption, stirring during mixing, the stirring time is 0.5 to 2.5 hours, and the stirring speed is 100 to 500 rpm.
[0030] Description: Controlling the sulfuric acid concentration can effectively desorb phosphoric acid from the ionic liquid-loaded resin, ensuring desorption efficiency. Sulfuric acid is a strong acid that can effectively compete with phosphoric acid for adsorption sites, thereby achieving efficient desorption; a reasonable volume ratio ensures sufficient contact between the desorbent and the resin, improving the desorption effect; this volume ratio allows the sulfuric acid solution to fully cover the resin particles, thereby achieving efficient desorption; controlling the appropriate stirring time ensures that the desorption reaction proceeds fully, avoiding incomplete desorption due to too short a time, and also avoiding energy waste caused by too long a time; within this time period, the resin particles and the sulfuric acid solution have enough time to react, thereby achieving a high desorption rate; an appropriate stirring speed can ensure uniform mixing between the desorbent and the resin, improving desorption efficiency; under appropriate sulfuric acid concentration and stirring conditions, the desorption process causes less damage to the resin structure, helping to maintain the adsorption capacity and service life of the resin.
[0031] The beneficial effects of the present invention are:
[0032] The present invention enhances the active sites of the resin and improves the reaction efficiency of the resin with glycine by pretreating the chloromethylated polystyrene resin. The use of a constant temperature magnetic stirrer ensures the uniformity and stability of the reaction conditions, thereby improving the reaction conversion rate and the purity of the product. The glycine ionic liquid-loaded resin is used to purify phosphoric acid, with a high recovery rate, avoiding emulsification, reducing solvent loss, being environmentally friendly, and having excellent recyclability. The prepared ionic liquid-loaded resin has good stability and reusability, thereby extending the service life of the material. The process is simple, easy to implement automatic control, and improves production efficiency and sustainability. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is a bar graph showing adsorption performance tests of samples of Examples 1 to 11 and Comparative Examples 1 to 8 of the present invention;
[0034] Figure 2 It is a bar graph of the adsorption selectivity test of samples of Examples 1 to 11 of the present invention and Comparative Examples 1 to 8. DETAILED DESCRIPTION
[0035] In order to further illustrate the approach and effects achieved by the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with experiments.
[0036] Example 1:
[0037] A method for preparing an ionic liquid-loaded resin comprises the following steps:
[0038] S1. Pretreatment of chloromethylated polystyrene resin
[0039] The chloromethylated polystyrene resin was soaked in an ethanol solution at a ratio of 2:1 ml / g for 2.5 hours, washed, and then dried to obtain a pretreated chloromethylated polystyrene resin; the chloromethylated polystyrene resin was prepared in the form of particles having a particle size of 150 μm;
[0040] The volume concentration of the ethanol solution is 97%; the washing and drying method is as follows: soaking the resin in deionized water for 1.5 hours, washing the chloromethylated polystyrene resin with deionized water, and then placing the washed chloromethylated polystyrene resin in a vacuum drying oven and drying it at 60°C for 4.5 hours;
[0041] S2. Prepare glycine solution
[0042] Mix glycine and water, and stir until completely dissolved to obtain a glycine solution with a mass concentration of 20%;
[0043] S3. Preparation of ionic liquid loaded resin
[0044] The pretreated chloromethylated polystyrene resin and glycine solution were introduced into a reactor, heated and stirred using a constant temperature magnetic stirrer, cooled after the synthesis reaction was completed, and the solid-liquid mixture in the reactor was subjected to solid-liquid separation. The filtered solid matter was then washed with deionized water and then placed in a vacuum drying oven for drying to obtain an ionic liquid-loaded resin;
[0045] The introduction ratio of the glycine solution to the chloromethylated polystyrene resin was 40:1 ml / g; the heating temperature of the constant temperature magnetic stirrer was 85° C., and the stirring time was 18 h;
[0046] The solid-liquid separation method comprises: filtering the solid-liquid mixture in the reaction kettle with a quantitative medium-speed filter paper, and when no obvious liquid drips out of the filter paper, washing the filtered solid matter with deionized water by a flushing method for 10 times to complete the solid-liquid separation of the ionic liquid loaded resin;
[0047] Auxiliary microspheres accounting for 13% of the mass ratio of the pretreated chloromethylated polystyrene resin are also added to the reactor;
[0048] The auxiliary microspheres are prepared by mixing sterile absorbent cotton and a 50% sulfuric acid solution in a mass ratio of 4:6, stirring and hydrolyzing at 45°C; adding water to a mixed solution obtained after the hydrolysis is completed, with the mass ratio of the mixed solution to water being 1:10; standing for 11 hours, removing the supernatant, and centrifuging the remaining mixed solution; filtering and washing with deionized water and a filter membrane, adding TMOS accounting for 4% of the mass of the mixed solution until the pH reaches 2.4, stirring for 2 hours, introducing the mixed solution into a spherical mold with an average particle size of 2.5 mm for freeze molding, and demolding at 525°C to obtain aerogel particles; immersing the aerogel particles in a 17.5% lanthanum nitrate hexahydrate solution, heating the solution in a water bath at 60°C for 30 hours, drying the solution, and calcining the solution for 6 hours to obtain auxiliary microspheres;
[0049] The stirring hydrolysis time is 2 hours, the stirring rate is 300 rpm; the centrifugal speed is 10500 rpm; the freeze molding method is: placing the spherical mold at 1.5°C for freeze molding for 5 hours, and then placing it in a freeze dryer at 10°C for freeze drying for 30 hours; the drying temperature is 80°C, the drying time is 1.75 hours, and the calcination temperature is 550°C.
[0050] The application method of the ionic liquid-loaded resin for selective phosphorus adsorption is as follows: the prepared ionic liquid-loaded resin is placed in a multi-metal ion solution with a concentration of 4.5 mol / L, and adsorption is carried out at an oscillation frequency of 120 r / min. The mixing ratio of the phosphoric acid solution and the ionic liquid-loaded resin is 40:1 ml / g, the temperature is maintained at 30°C, and the adsorption time is 6 hours. The resin is then subjected to solid-liquid separation, and finally the extracted phosphoric acid-containing ionic liquid-loaded resin is desorbed to obtain a phosphoric acid-containing solution. The multi-metal ion solution is an aqueous solution of metal ions containing iron, magnesium, aluminum, and phosphorus.
[0051] The desorption treatment method is as follows: using a sulfuric acid solution with a concentration of 5 mol / L as a desorbent, mixing the phosphoric acid-containing ionic liquid loaded resin and the sulfuric acid solution at a volume ratio of 1:30 for desorption, stirring during mixing, the stirring time is 1.5 hours, and the stirring speed is 300 rpm.
[0052] Example 2: This example is basically the same as Example 1, except that auxiliary microspheres accounting for 2% by mass of the pretreated chloromethylated polystyrene resin are further added to the reactor.
[0053] Example 3: This example is basically the same as Example 1, except that auxiliary microspheres accounting for 25% by mass of the pretreated chloromethylated polystyrene resin are further added to the reactor.
[0054] Example 4: This example is basically the same as Example 1, except that sterile absorbent cotton and a 45% volume concentration sulfuric acid solution are mixed in a mass ratio of 4:5 and stirred for hydrolysis at a temperature of 40°C; after the hydrolysis is completed, a mixed solution is obtained, water is added, and the mass ratio of the mixed solution to water is 1:8; the mixture is allowed to stand for 10 hours, the supernatant is removed, and the remaining mixed solution is centrifuged; it is then filtered and washed with deionized water and a filter membrane, and when the pH reaches 2.4, 3% TMOS by mass of the mixed solution is added, stirred for 1 hour, and introduced into a spherical mold with an average particle size of 2 mm for freeze molding, and demolded at 500°C to obtain aerogel particles; the aerogel particles are immersed in a 5% concentration of lanthanum nitrate hexahydrate solution and heated in a water bath at 50°C for 25 hours; dried and calcined for 5 hours to obtain auxiliary microspheres.
[0055] Example 5: This example is basically the same as Example 1, except that sterile absorbent cotton and a 55% volume concentration sulfuric acid solution are mixed in a mass ratio of 4:7 and stirred for hydrolysis at a temperature of 50°C; after the hydrolysis is completed, a mixed solution is obtained, water is added, and the mass ratio of the mixed solution to water is 1:12; the mixture is allowed to stand for 12 hours, the supernatant is removed, and the remaining mixed solution is centrifuged; it is then filtered and washed with deionized water and a filter membrane, and when the pH reaches 2.4, 5% TMOS by mass of the mixed solution is added, stirred for 3 hours, and introduced into a spherical mold with an average particle size of 3 mm for freeze molding, and demolded at 550°C to obtain aerogel particles; the aerogel particles are immersed in a 30% concentration of lanthanum nitrate hexahydrate solution, heated in a water bath at 70°C for 35 hours, dried, and calcined for 7 hours to obtain auxiliary microspheres.
[0056] Example 6: This example is basically the same as Example 1, except that the mixing ratio of the ethanol solution and the chloromethylated polystyrene resin is 1.5:1 ml / g.
[0057] Example 7: This example is basically the same as Example 1, except that the mixing ratio of the ethanol solution and the chloromethylated polystyrene resin is 2.5:1 ml / g.
[0058] Example 8: This example is basically the same as Example 1, except that the introduction ratio of the glycine solution to the chloromethylated polystyrene resin is 20:1 ml / g.
[0059] Example 9: This example is basically the same as Example 1, except that the introduction ratio of the glycine solution to the chloromethylated polystyrene resin is 60:1 ml / g.
[0060] Example 10: This example is basically the same as Example 1, except that the prepared ionic liquid-loaded resin is placed in a multi-metal ion solution with a concentration of 4.5 mol / L, and oscillation adsorption is performed at an oscillation frequency of 110 r / min. The mixing ratio of the phosphoric acid solution and the ionic liquid-loaded resin is 20:1 ml / g, the temperature is maintained at 25°C, and the adsorption time is 4 h; then solid-liquid separation is performed, and finally the extracted phosphoric acid-containing ionic liquid-loaded resin is desorbed to obtain a phosphoric acid-containing solution.
[0061] Example 11: This example is basically the same as Example 1, except that a sulfuric acid solution with a concentration of 4 mol / L is used as a desorbent, and the phosphoric acid-containing ionic liquid-loaded resin and the sulfuric acid solution are mixed and desorbed at a volume ratio of 1:28. The mixture is stirred for 0.5 h at a stirring speed of 100 rpm.
[0062] Example 12: This example is basically the same as Example 1, except that the prepared ionic liquid-loaded resin is placed in a multi-metal ion solution with a concentration of 4.5 mol / L, and oscillation adsorption is performed at an oscillation frequency of 130 r / min. The mixing ratio of the phosphoric acid solution and the ionic liquid-loaded resin is 60:1 ml / g, the temperature is maintained at 35°C, and the adsorption time is 8 h; then solid-liquid separation is performed, and finally the extracted phosphoric acid-containing ionic liquid-loaded resin is desorbed to obtain a phosphoric acid-containing solution.
[0063] Example 13: This example is basically the same as Example 1, except that a sulfuric acid solution with a concentration of 6 mol / L is used as a desorbent, and the phosphoric acid-containing ionic liquid-loaded resin and the sulfuric acid solution are mixed and desorbed in a volume ratio of 1:32. The mixture is stirred for 2.5 h at a stirring speed of 500 rpm.
[0064] Comparative Example 1: Using Example 1 as a reference, no auxiliary microspheres were added to the reactor.
[0065] Comparative Example 2: Taking Example 1 as a reference, auxiliary microspheres accounting for 29% by mass of the chloromethylated polystyrene resin were added to the reactor described in S3.
[0066] Comparative Example 3: Using Example 1 as a reference, sterile absorbent cotton and a 30% volume concentration sulfuric acid solution were mixed in a mass ratio of 4:4.5, and stirred and hydrolyzed at a temperature of 35°C; after the hydrolysis was completed, a mixed solution was obtained, water was added, and the mass ratio of the mixed solution to water was 1:7; the mixture was allowed to stand for 9 hours, the supernatant was removed, and the remaining mixed solution was centrifuged; then it was filtered and washed with deionized water and a filter membrane, and when the pH reached 2.4, 2% TMOS by mass of the mixed solution was added, stirred for 0.5 hours, and introduced into a spherical mold with an average particle size of 1.5 mm for freeze molding, and demolded at 600°C to obtain aerogel particles; the aerogel particles were immersed in a 4% concentration of lanthanum nitrate hexahydrate solution and heated in a water bath at 40°C for 20 hours; dried and calcined for 4 hours to obtain auxiliary microspheres.
[0067] Comparative Example 4: Taking Example 1 as a reference, the mixing ratio of the ethanol solution and the chloromethylated polystyrene resin is 1.5-2.5:1 ml / g.
[0068] Comparative Example 5: Using Example 1 as a reference, the introduction ratio of the glycine solution to the chloromethylated polystyrene resin is 20-60:1 ml / g.
[0069] Comparative Example 6: Using Example 1 as a reference, glycine and water in S2 and S3 were replaced by pyridine and N,N-dimethylformamide.
[0070] Control Example 7: Using Example 1 as a reference, the prepared ionic liquid-loaded resin was placed in a multi-metal ion solution with a concentration of 4.5 mol / L, and oscillation adsorption was performed at an oscillation frequency of 100 r / min. The mixing ratio of the phosphoric acid solution and the ionic liquid-loaded resin was 15:1 ml / g, the temperature was maintained at 20°C, and the adsorption time was 3.5 h; then, solid-liquid separation was performed, and finally, the extracted phosphoric acid-containing ionic liquid-loaded resin was desorbed to obtain a phosphoric acid-containing solution.
[0071] Comparative Example 8: Using Example 1 as a reference, a sulfuric acid solution with a concentration of 3.5 mol / L was used as a desorbent, and the phosphoric acid-containing ionic liquid-loaded resin and the sulfuric acid solution were mixed and desorbed at a volume ratio of 1:27. The mixture was stirred for 0.4 h at a stirring speed of 90 rpm.
[0072] In order to explore the performance of the ionic liquid-loaded resins produced in Examples 1 to 7, 12, and 13 and Comparative Examples 1 to 8, the main materials were determined according to the experimental formula and 13 groups of samples were prepared for testing. The specific exploration is as follows:
[0073] Condition 1 is the first adsorption capacity test of the sample; Condition 2 is the 100th adsorption capacity test of the same sample.
[0074] 1. Investigate the effect of auxiliary microsphere ratio on the performance of ionic liquid loaded resin:
[0075] like Figure 1 、 Figure 2 As shown, by comparing Examples 1 to 3, it can be seen that Example 1 has better comprehensive performance; changing the auxiliary microsphere ratio parameters will have a certain impact on the prepared ionic liquid loaded resin sample, among which the ionic liquid loaded resin prepared with process parameter values close to Example 1 has better comprehensive performance.
[0076] Compared with Control Examples 1 and 2, it can be seen that the addition of auxiliary microspheres can enhance the efficiency of adsorbing phosphoric acid, and the adsorption performance of samples with the auxiliary microsphere content controlled within the range of this method is better.
[0077] 2. Investigate the effects of process parameters for auxiliary microsphere preparation on the performance of ionic liquid loaded resin:
[0078] like Figure 1 、 Figure 2 As shown, by comparing Examples 1, 4, and 5, it can be seen that: Example 1 has the best comprehensive performance; Example 4 has better adsorption performance than Example 5. Changing the process parameters for preparing the auxiliary microspheres will have a certain impact on the prepared ionic liquid-loaded resin sample, among which the ionic liquid-loaded resin prepared by the process parameter values closer to Example 1 has the best comprehensive performance.
[0079] like Figure 1 、 Figure 2 As shown, by comparing Example 1 and Control Example 3, it can be seen that the comprehensive performance of Example 1 is significantly better than that of Control Example 3. Compared with the process parameters of Control Example 3, the sample prepared using the parameters within the range of this method has better adsorption performance.
[0080] 3. Investigate the effect of the resin preparation ratio parameters on the performance of ionic liquid loaded resin:
[0081] like Figure 1 、 Figure 2 As shown, by comparing Examples 1, 6, and 7, it can be seen that the ionic liquid-loaded resin prepared according to the method of Example 1 has the best comprehensive performance, and Example 7 is better than Example 6. It can be seen that the ratio parameters for preparing the resin can have a certain impact on the performance of the ionic liquid-loaded resin, and controlling the appropriate ratio can improve its adsorption performance.
[0082] From the comparison between Example 1 and Control Examples 4 and 5, it can be seen that the adsorption performance of Example 1 is significantly better than that of Control Examples 4 and 5. The mixing ratio of ethanol solution and chloromethylated polystyrene resin and the introduction ratio of glycine solution and chloromethylated polystyrene resin have a significant effect on the effect of ionic liquid loading on the resin.
[0083] 4. Investigate the effects of application process parameters on the performance of ionic liquid loaded resins:
[0084] like Figure 1 、 Figure 2 As shown, by comparing Examples 1, 10, and 11, it can be seen that the adsorption performance of Examples 1, 10, and 11 is similar, and the ionic liquid-loaded resin applied according to the method of Example 1 has the best weather resistance. The applied process parameters have a certain influence on the performance of the ionic liquid-loaded resin, but the effect is not obvious. Compared with Control Example 7, Example 1 has a more obvious difference in adsorption, and a small difference in durability. Compared with Control Example 8, the difference in adsorption is not obvious, and the difference in durability is large. It can be seen that the application method has a greater influence on the adsorption, and the desorption method has a greater influence on the durability. Among them, the method parameters used in Example 1 are the best.
[0085] After testing the sample applications of Examples 1 to 3, the average MER of the multi-metal ion solution used before adsorption treatment was 8.24, and the average MER of the phosphoric acid-containing solution after desorption treatment with the ionic liquid-loaded resin was 0.68. After preparation and treatment using this method, the adsorption, purification and reuse effect of phosphoric acid can be greatly improved.
Claims
1. An application of an ionic liquid loaded resin in selective adsorption of phosphorus, characterized in that: The preparation method of the ionic liquid loaded resin comprises the following steps: S1. Pretreatment of chloromethylated polystyrene resin Soaking chloromethylated polystyrene resin in an ethanol solution at a ratio of 1:1.5-2.5 g / ml for 2-3 hours, washing, and drying to obtain a pretreated chloromethylated polystyrene resin; the chloromethylated polystyrene resin has a particle size of 100-200 μm; S2. Prepare glycine solution Mix glycine with water and stir until completely dissolved to obtain a glycine solution with a mass concentration of 10-30%; S3. Preparation of ionic liquid loaded resin The pretreated chloromethylated polystyrene resin and glycine solution are introduced into a reactor at a ratio of 1:20~60g / ml, heated and stirred using a constant temperature magnetic stirrer, the heating temperature is 65~105℃, and the stirring time is 6~30h. After the synthesis reaction is completed, the mixture is cooled, and the solid-liquid mixture in the reactor is solid-liquid separated. The filtered solid matter is washed with deionized water and then placed in a vacuum drying oven for drying to obtain an ionic liquid-loaded resin; auxiliary microspheres accounting for 2~25% of the mass ratio of the pretreated chloromethylated polystyrene resin are also added to the reactor; the preparation method of the auxiliary microspheres is as follows: sterile absorbent cotton and a sulfuric acid solution with a volume concentration of 45~55% are mixed at a mass ratio of 4:5 ~7, stirred and hydrolyzed at a temperature of 40~50℃; after the hydrolysis, a mixed solution was obtained, water was added, and the mass ratio of the mixed solution to water was 1:8~12; the mixture was allowed to stand for 10~12 hours, the supernatant was removed, and the remaining mixed solution was centrifuged; it was then filtered and washed with deionized water and a filter membrane, and when the pH reached 2.4, TMOS accounting for 3~5% of the mass of the mixed solution was added, stirred for 1~3 hours, and introduced into a spherical mold with an average particle size of 2~3mm for freeze molding, and demolded at 500~550℃ to obtain aerogel particles; the aerogel particles were immersed in a solution of lanthanum nitrate hexahydrate with a concentration of 5~30%, heated in a water bath at 50~70℃ for 25~35 hours, dried, and calcined for 5~7 hours to obtain auxiliary microspheres; The application method of the ionic liquid-loaded resin comprises: placing the prepared ionic liquid-loaded resin into a multi-metal ion solution with a concentration of 4.5 mol / L, performing oscillation adsorption at an oscillation frequency of 110 to 130 r / min, wherein the mixing ratio of the multi-metal ion solution to the ionic liquid-loaded resin is 20 to 60:1 ml / g, the temperature is maintained at 25 to 35° C., and the adsorption time is 4 to 8 hours; then performing solid-liquid separation, and finally desorbing the extracted phosphoric acid-containing ionic liquid-loaded resin to obtain a phosphoric acid-containing solution; The desorption treatment method comprises: using a sulfuric acid solution with a concentration of 4 to 6 mol / L as a desorbent, mixing the phosphoric acid-containing ionic liquid-loaded resin and the sulfuric acid solution at a volume ratio of 1:28 to 32 for desorption, and stirring during mixing for 0.5 to 2.5 hours at a stirring speed of 100 to 500 rpm.
2. The use of an ionic liquid loaded resin in selective adsorption of phosphorus according to claim 1, characterized in that: The volume concentration of the ethanol solution in S1 is 95-99%; the washing and drying method is: soaking in deionized water for 1-2 hours, then washing the chloromethylated polystyrene resin with deionized water, and then placing the washed chloromethylated polystyrene resin in a vacuum drying oven and drying it at a temperature of 55-65°C for 4-5 hours.
3. Use of an ionic liquid loaded resin in selective adsorption of phosphorus according to claim 1, characterized in that: The solid-liquid separation method described in S3 is: filtering the solid-liquid mixture in the reactor with quantitative medium-speed filter paper, and when no obvious liquid drips out of the filter paper, washing the filtered solid matter with deionized water by flushing for 8 to 12 times to complete the solid-liquid separation of the ionic liquid loaded resin.
4. The use of an ionic liquid loaded resin in selective adsorption of phosphorus according to claim 1, characterized in that: In the preparation method of the auxiliary microspheres, the stirring hydrolysis time is 1.5 to 2.5 hours, the stirring rate is 200 to 400 rpm, the centrifugal speed is 10,000 to 11,000 rpm, the freeze-molding method is: the spherical mold is placed at -5 to -8°C and frozen for 4 to 6 hours, and then placed in a freeze dryer at -75 to -95°C and freeze-dried for 25 to 35 hours; the drying temperature is 70 to 90°C, the drying time is 0.5 to 3 hours, and the calcination temperature is 500 to 600°C.
Citation Information
Patent Citations
Heavy metal ion adsorbent for grafting glycine to chloromethylated polystyrene, preparation method and application thereof
CN104209102A
Lanthanum modified mesoporous silica aerogel as well as preparation method and application thereof
CN110394150A